Characteristics of Emotional Expression in Primary School Children and Its Management from the Perspective of the Teaching Staff - Cassinda-Vissupe, María Domingas (2017)
The research aimed to characterize the emotional expression of primary school children, events linked to its manifestation and its management from the perspective of the teaching staff. For this descriptive exploratory study, a non-probabilistic sample of 53 teachers from various primary schools was conformed. The study was carried out by using the analysis of documents, interviews and observation, and implementing the content analysis for interpretation. Teachers identified a predominance of pleasant emotions in school, mainly joy. The main unpleasant emotions were anxiety and anger. In the school context, the unpleasant emotions were associated with the activities and the academic demands; in the family, with conflict and little family support, fundamentally. The principal drivers of pleasant emotions in school are the group acceptance, teacher professionalism and recreation; the latter is also present in the family, together with the support, dedication and harmonious coexistence. The professor says not to possess the necessary theoretical and methodological training to direct the emotional education of their students, although they recognize its importance. It is very important to provide a more solid training that allows them to know, understand and regulate their emotions as well as enhance the emotional development of their students, creating an emotional environment which facilitates the process of learning.